RANCANG BANGUN 4 DOF (DEGREE OF FREEDOM) UNDERWATER REMOTELY OPERATED VEHICLE (ROV) - Rachmansyah, Yoki; Rahmat, Mamat; Ahmad, Anton Royanto; Nuraini, Aisyah Iadha (ALMIKANIKA, 2019)
In this research, the underwater robot designed is a type of mini Remotely Operated Vehicle (ROV) based on the Arduino Uno Atmega 328A microcontroller. This research was aimed to make a robot underwater or ROV and test its performance in water. This research was conducted to determine the system of tightness in the ROV by using a body that was used as a cover for each component in the ROV and tested its movement in the water. The design of mini ROVs is integrated in several design processes, namely planning the calculation of each component selection used by ROV, designing mechanical construction, designing electronic construction, and making integration of the entire design process. The results of this integration are in the form of a physical form of mini ROV, electronic systems, and graphical interface programs. The designed robot is an underwater robot that can move in water with the X, Y and Z axes. The ROV robot is made with a total dimension of 38 cm in length, 21 cm in width, and 22 cm in height. The body of the ROV is made using a base material from a PVC pipe that each gap is lined with a seal so that the ROV can be maintained properly. In the ROV movement system, use 2 propeller leaves to go forward and backward and 2 propeller leaves to drown or raise the ROV.